5G wireless technologies. - Alexiou, Angeliki (IET telecommunications series ;, 2017)
Mobile data traffic is expected to exceed traffic from wired devices in the next couple of years. This emerging future will be empowered by revolutionary 5G radio network technologies with a focus on application-driven connectivity, transparently deployed over various technologies, infrastructures, users and devices to realise the vision of 'the Internet of Everything'. This book presents a roadmap of 5G, from advanced radio technologies to innovative resource management approaches and novel network architectures and system concepts. Topics covered include challenges for efficient multi-service coexistence for 5G below 6GHz; new quasi-deterministic approaches to channel modelling in millimetre-wave bands; large scale antenna systems; effects of densification and randomness of infrastructure deployment in cellular networks; wireless device-to-device (D2D) Links for machine-to-machine (M2M) communication; caching in large wireless networks; full duplexing; decoupled uplink and downlink access in heterogeneous networks; wireless networks virtualisation; and regulation, business and technology perspectives on licensed shared access (LSA) and three-tier spectrum sharing models. 5G Wireless Technologies is an essential guide to this emerging system for researchers, engineers and advanced students working in telecommunications and networking.